Association of Vitamin D Levels in Chronic Obstructive Pulmonary Disease - Mahammad Rafi, Vempalli; Andrew R, Sanjay; Ashok Vardhan, Nandigam (Journal of Neonatal Surgery, 2025)
Chronic obstructive pulmonary disease is a prevalent respiratory condition with persistent airflow limitation and significant morbidity. Emerging evidence suggests vitamin D deficiency may play a role in the disease's pathogenesis and progression. This review examines the relationship between vitamin D status and COPD, including potential mechanisms by which vitamin D may influence disease outcomes and implications for clinical management. Observational studies consistently report an association between low vitamin D levels and increased COPD risk, as well as poorer outcomes like exacerbations, hospitalizations, and mortality. Proposed mechanisms include vitamin D's anti-inflammatory, antioxidant, and immune-modulatory effects, as well as its impact on respiratory muscle function. However, randomized trials on vitamin D supplementation have shown mixed results. Further research is needed to clarify vitamin D's role in COPD, including optimal serum levels and personalized approaches. In the meantime, clinicians should consider screening for vitamin D deficiency and providing supplementation as part of comprehensive COPD management.